Hepatic abscess in inflammatory bowel disease: A systematic scoping review of an overlooked entity - Shadi Abdullah Alshammary; Dhuha Nahar Boumarah (Saudi Journal of Medicine and Medical Sciences, 2023)
Background: Liver abscess is one of the hepatobiliary manifestations of inflammatory bowel disease (IBD) that has been scarcely described in the literature. Objectives: To conduct a scoping review to provide a detailed description of the occurrence of hepatic abscess in patients with IBD and summarize the observed clinical features. Methodology: Searches were carried out using relevant keywords in Medline (via PubMed) and Web of Science from inception until June 13, 2022. Only articles that reported the occurrence of hepatic abscess in patients with IBD were included. Results: Forty-eight publications (40 case reports and 8 case series) were included, representing 73 patients with IBD who were radiologically or intraoperatively diagnosed with hepatic abscess. Patients with Crohn's disease were more predisposed to developing hepatic abscess than patients with ulcerative colitis (79.5% vs. 20.5%, respectively). Furthermore, pyogenic liver abscess was found to be more prevalent (57.9%) compared with aseptic (38.7%) and amebic (3.2%) abscesses. No clear relation was found between death or prolonged hospital stay in terms of the clinical presentation or management plan, as mortality was reported in different age groups with different managements. Conclusion: To date, there is no consensus regarding the appropriate management of hepatic abscess as an extraintestinal manifestation of IBD. However, the condition shares several features with liver abscess diagnosed among the general population.